2004
DOI: 10.1507/endocrj.51.517
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Treatment of Acromegaly with Lanreotide: Evidence of Increased Serum Parathormone Concentration

Abstract: Abstract. The somatostatin analogue lanreotide is effective in reducing growth hormone levels in patients with acromegaly. Acromegaly is characterized by calcium homeostasis alterations. The aim of our study was to evaluate the effects of lanreotide on bone turnover markers in a group of acromegalic patients and to verify a possible increase of intact parathormone (iPTH) levels in a transient or persistent way. Serum GH, IGF-I and serum and urinary markers of bone metabolism were measured before treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
(31 reference statements)
2
11
0
1
Order By: Relevance
“…Even in normocalcemic acromegaly patients, we identified changes of calciumphosphate balance after treatment of acromegaly: a decrease in mean serum and urine calcium, along with a decrease in phosphorus levels. This is consistent with previous studies that indicated a decrease in serum calcium level at 3 to 4 weeks after pituitary surgery (8) and 3 to 4 months after treatment with somatostatin analogs (7,10). The role of 1,25(OH) 2 D in calcium perturbations in acromegaly has been attributed to the activation of renal 1-a-hydroxylase by GH (25) or PRL (26).…”
Section: Calcium Changes In Acromegalysupporting
confidence: 91%
See 3 more Smart Citations
“…Even in normocalcemic acromegaly patients, we identified changes of calciumphosphate balance after treatment of acromegaly: a decrease in mean serum and urine calcium, along with a decrease in phosphorus levels. This is consistent with previous studies that indicated a decrease in serum calcium level at 3 to 4 weeks after pituitary surgery (8) and 3 to 4 months after treatment with somatostatin analogs (7,10). The role of 1,25(OH) 2 D in calcium perturbations in acromegaly has been attributed to the activation of renal 1-a-hydroxylase by GH (25) or PRL (26).…”
Section: Calcium Changes In Acromegalysupporting
confidence: 91%
“…Treatment of acromegaly with surgery (2) or a GH receptor antagonist (8) resulted in a reduction of mean 1,25(OH) 2 D levels, whereas GH supplementation in GH-deficient adults had the opposite effect (27). On the other hand, a reduction of mean 1,25(OH) 2 D levels has not been found in longitudinal studies where patients were treated with somatostatin analogs (10,11 (5). The patient population enrolled in prior studies was heterogeneous with regards to the duration and biochemical severity of acromegaly, while assays for IGF-1 and 1,25(OH) 2 D have also evolved.…”
Section: Calcium Changes In Acromegalymentioning
confidence: 99%
See 2 more Smart Citations
“…Mean 25OH-D3 levels did not change during short and long-term SA therapy, suggesting that long-term SA therapy does not affect serum vitamin D [59]. Similar data were found by Cappelli et al, who demonstrated that 24 months of treatment with lanreotide in 35 patients with acromegaly did not associate with significant changes in 1,25(OH)2-D3 levels [68]. Conversely, only during the short-term treatment (8 and 14 days) with octreotide, was a rise shown in mean serum 1,25(OH)2-D3, with no changes in VDBP [69].…”
Section: Impact Of Acromegaly Treatment On Vitamin D Levelssupporting
confidence: 82%